ADHD and comorbidity: The role of pharmacotherapy - Doulou, Aikaterini; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
In recent years, there has been an increase in the incidence of ADHD in children and adolescents. Many learning and behavioral problems are associated with this disorder due to difficulties in cognitive and metacognitive functions. Only when individuals improve these functions will they be able to integrate in the social environment. Skills such as self-awareness, self-regulation, and self-control can help children with ADHD develop their emotional intelligence to control their cognitive deficits and adapt to diverse areas. With the rapid development of science, several medical and behavioral methods have been proposed to treat ADHD, which have contributed significantly to the control of symptoms. However, medication is considered as a first-choice treatment to reduce the symptoms. The present study investigates the comorbidity of ADHD with other mental and developmental disorders as also the role and effectiveness of drug intervention in order to improve the quality of life of these children.